Composing meaning through multiliteracies and multimodality with adolescent and adult learners - Holloway, Susan M.; Qaisi, Rasha (Language and Literacy / Langue et littératie, 2022)
The research from this ongoing nationally funded study explores multiliteracies and multimodality in secondary schools and adult education settings including a museum, dance studio, and French language learning centre. There are 30 participants to date in the study. Using constructivist grounded theory methodology, the study draws upon data from face-to-face interviews, observations, document analysis, and original film footage of learning spaces. Social semiotics theory is used in this paper to articulate how a range of modes (visual, linguistic, and gestural) affect teaching and learning. The findings suggest that multiliteracies and multimodality foster creativity and criticality, engage marginalized learners, and provide greater versatility in meaning-making practices.